PENGEMBANGAN MEDIA CERITA ALKITAB UNTUK BINA IMAN ANAK KATOLIK BERBASIS POP-UP BOOK - Ellen, Patricia; Permana, Natalis Sukma (Bahasa Indonesia, 2025)
This study aims to determine the feasibility of Pop-up Book as a Bible story media based on the blibical story about creation for children faith formation. The development of media story based on the Pop-up Book Bible story was motivated by the need of a creative media to teach the Word of God for the Catholic children faith formation. This research applied the research and development method referring to the Borg and Gall’s model through ten steps, namely research and data collection, planning, product draft development, limited trial, product revision stage, extensive trial stage, operational product revision, operational trial, final product revision, dissemination, and implementation. Research data was collected through observations, interviews, and questionnaires. The targets of the research were children at 7-12 years old belong to Mater Dei Parish, Madiun, and Saint Hilarius Parish, Klepu. The study showed that the results of assessment conducted by material experts, and media practitioners, as well as the positive responses of the children during the field trials on the Pop-up Book as a Bible story media based on the blibical story about creation for children faith formation was graded “Very Good”, and then can be applied in the Catholic children faith formation activities.